2020
DOI: 10.1039/d0ra00227e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of caffeic acid sulfonamide derivatives and their protective effect against H2O2 induced oxidative damage in A549 cells

Abstract: Synthesized caffeic acid derivatives exhibit protective effect on H2O2 induced oxidative injury in A549 cells via Nrf2 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This results in the elimination of reactive oxygen species (ROS), alteration of glutathione homeostasis, up-regulation of the expression of antioxidant response element dependent genes and enhancement of antioxidant defence mechanism [ 1 , 109 , 110 ]. Peng and co-workers [ 111 ] reported that caffeic acid sulfonamide derivatives ( 8 , 9 , 10 ) ( Table 1 ), when used in the treatment of H 2 O 2 -stimulated A549 cells, enhance mRNA expression of Nrf2 and its target genes. Naphthalene sulphonamide derivatives compound are notable Nrf2 activators.…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…This results in the elimination of reactive oxygen species (ROS), alteration of glutathione homeostasis, up-regulation of the expression of antioxidant response element dependent genes and enhancement of antioxidant defence mechanism [ 1 , 109 , 110 ]. Peng and co-workers [ 111 ] reported that caffeic acid sulfonamide derivatives ( 8 , 9 , 10 ) ( Table 1 ), when used in the treatment of H 2 O 2 -stimulated A549 cells, enhance mRNA expression of Nrf2 and its target genes. Naphthalene sulphonamide derivatives compound are notable Nrf2 activators.…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…In addition, other biological activities of the sulfonamide-based compounds have been reported, including antiradical, antioxidant, and neuroprotective properties. Sulfonamide derivatives were reported as anti-Alzheimer agents with antioxidant properties along with other possible mechanisms relating to cellular protection (Göçer et al, 2013;Leechaisit et al, 2019;Peng et al, 2020;Gök et al, 2021). According to the literature, sulfonamide derivatives have the potential to be used in the treatment of neurological disorders due to their antioxidant properties, which are the fundamental mechanism of neuroprotection (Göçer et al, 2013;Lee et al, 2020;Peng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamide derivatives were reported as anti-Alzheimer agents with antioxidant properties along with other possible mechanisms relating to cellular protection (Göçer et al, 2013;Leechaisit et al, 2019;Peng et al, 2020;Gök et al, 2021). According to the literature, sulfonamide derivatives have the potential to be used in the treatment of neurological disorders due to their antioxidant properties, which are the fundamental mechanism of neuroprotection (Göçer et al, 2013;Lee et al, 2020;Peng et al, 2020). However, these findings have not been tested in human neural cells for neuroprotective purposes, and the underlying mechanism in neuronal cells is yet unknown.…”
Section: Introductionmentioning
confidence: 99%